Self-Diffusion Coefficient of Ions in Battery Materials under Operating Condition Probed by μSR - Sugiyama, Jun; Ohishi, Kazuki; Umegaki, Izumi (Butsuri, 2024)
In this report, the self-diffusion coefficient of Li+(D JLi) and Na+(D JNa) in Lix CoO2 and P2-Nax CoO2 were measured during charge and discharge reactions between Lix CoO2 and Li metal electrodes and P2-Nax CoO2 and Na metal electrodes in the electrochemical half-cell using an operando muon spin rotation and relaxation ( μSR) technique through the observation of a fluctuating nuclear magnetic field.